Turning Complaining Customers into Loyal Customers: Moderators of the Complaint Handling–Customer Loyalty Relationship. (September 2020) - Morgeson, Forrest V.; Hult, G. Tomas M.; Mithas, Sunil; Keiningham, Timothy; Fornell, Claes
Firms spend substantial resources responding to customer complaints, and the marketing profession has a long history of supporting that enterprise to promote customer loyalty. The authors question whether this response is always warranted or whether its effectiveness instead depends on economic, industry, customer–firm, product/service, and customer segment factors that may alter the firm's incentives to compete on complaint management. To consider this question, they integrate economic and marketing theories and investigate factors that influence the complaint recovery–customer loyalty relationship via a sample of 35, 597 complaining customers spanning a ten-year period across economic sectors, industries, and firms. Overall, the authors find that the recovery–loyalty relationship is stronger in faster-growing economies, for industries with more competition, for luxury products, and for customers with higher satisfaction and higher expectations of customization. Conversely, the recovery–loyalty relationship is weaker when customers' expectations of product/service reliability are higher, for manufactured goods, and for men compared with women. The authors discuss implications of these results for managers, policy makers, and researchers for more effective management of customer complaints.